Cortical Motor Output of Braille Reading Hand - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Focal transcranial magnetic stimulation (TMS) was used to map the motor cortical outputs to the right and left first dorsal interosseous (FDI) and right abductor digiti minimi (ADM) muscles of the reading hand in 6 blind proficient Braille readers studied at the National Institute of Neurological Disorders and Stroke, NIH, Bethesda, MD.